Doing things together? Analysis of health education materials to inform hepatitis C prevention among couples - Dwyer, Robyn; Fraser, Suzanne; Treloar, C. (Routledge, 2011)
Considerable effort has been expended in developing health education materials and programmes aimed at reducing transmission of hepatitis C virus (HCV) among people who inject drugs. Health education is considered more likely to be effective when it is targeted to defined segments of the population and when people actively identify with the messages presented. In this context, it is important to understand the health messages on offer in these materials. This article conducts a discourse analysis of an extensive corpus of Australian heath education literature on HCV to explore the kinds of messages these materials attempt to present. It questions the unexamined assumptions they include and it considers how effectively these materials address the social context of HCV transmission. It focuses on issues of individual and group conduct: in particular, because HCV transmission occurs commonly between sexual partners, on the place of couples who inject together in prevention education. The article concludes by arguing that these materials pay insufficient attention to couples, relying almost without exception, and despite a longstanding critique recommending new approaches, on the individual as the core unit of agency in HCV transmission and in turn prevention.